Robustness of multi-storey car parks under vehicle fire - Fang, C.; Izzuddin, B.A.; Obiala, R.; Elghazouli, A.Y.; Nethercot, D.A. (Journal of constructional steel research, 2012)
While recent studies on structures subject to fire have focused on individual structural members, sub-frames, or entire structures, issues of robustness due to the possible loss of columns exposed to fire have received less attention. This paper is concerned with the realistic modelling of a multi-storey car park under a vehicle fire scenario occurring near an internal column, where emphasis is given to the robustness and ductility response of the floor systems subsequent to column buckling. To address this, a detailed heat transfer analysis according to the proposed fire scenario is conducted to obtain realistic temperature distributions within the structure. For the subsequent structural analysis, two structural models with different modelling sophistications are established, namely, a detailed slab model and a simplified grillage model. Dynamic analysis is performed to trace potential dynamic effects, where the inelastic joint response is considered in detail for the purpose of robustness assessment. Based on the undertaken nonlinear analysis, three major failure modes, specifically single-span failure, double-span failure, and shear failure, are identified which can potentially trigger progressive collapse. Finally, the significance of dynamic effects along with column buckling under fire is evaluated, where it is found that the actual ductility demands fall between two idealised extreme cases, namely ‘static column loss’ and ‘sudden column loss’. ► Modelling of heat transfer arising from realistic car fire scenario. ► Realistic structural modelling using two different levels of idealisation. ► Modelling of joint ductility and progressive collapse resistance to localised fire. ► Dynamic effects following column buckling found to be potentially significant. ► Considered typical steel-composite car park found to be adequate.